The Effect of Health Education on Oxytocin Massage and Exclusive Breastfeeding on the Motivation of Exclusive Breastfeeding Mothers in the Working Area of Karang Ayu Health Center, Semarang. - Qomariyah Qomariyah; Kristina Maharani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Breast milk is a baby's main food that should be given exclusively for 6 months. The thing that can increase breast milk production is by doing oxytocin massage. The purpose of this study was to determine the effect of health education on Oxytocin Massage and Exclusive Breastfeeding on the Motivation of Exclusive Breastfeeding Mothers in the Working Area of Karang Ayu Semarang Health Center. This type of research is a Quasi Experiment, using an extended Pretest-Postest Group design approach involving one experimental group and one control group. The population in this study were all pregnant women at the Karang Ayu Semarang Health Center from January to March 2021. Samples were taken according to the inclusion and exclusion criteria. The results of the Wilcoxon test gave a P value of 0.000, meaning that there was an effect on the motivation of respondents before and after being given health education.